PENGARUH RELATIONSHIP MARKETING DAN PROMOSI TERHADAP CUSTOMER LOYALITY JASA TRANSPORTASI PADA TRAVEL CV. FLORES SIBOLGA - Hutriansyah Harahap; Mhd. Shafwan Koto; Rifka Hadia Lubis (CV. ALIM'SPUBLISHING, 2023)
This study aims to determine the effect of relationship marketing and promotion on customer loyalty in transportation services at Travel CV. Flores Sibolga. This research was conducted at Travel CV. Flores Sibolga, which is on Jalan Diponegoro No. 42 Sibolga District, Sibolga City. The time of the research was conducted from April 2022 to September 2022. The type of research used in this study is a type of quantitative descriptive research. The population is the total number of consumers using CV Travel transportation services. Flores Sibolga on average every day as many as 100 people. The number of research samples of 50 people was taken from the results of calculations with the slovin formula. The results of the research analysis are known from the calculation of the research instrument, the X and Y variables for each item are declared valid because the total corrected item value is greater than the critical r value (0.30). Calculation of the research data instrument, the results of the X and Y variables are declared reliable because Cronbach Alpha is above 0.60. The influence of Relationship Marketing and promotion on Customer Loyalty, the result of calculating the coefficient of determination is 0.707 = 50%, this means that what happens to the variation of the dependent variable (customer loyalty) is 50% determined by the independent variables (Relationship Marketing and promotions) and the remaining 50% determined by other variables not discussed in this study, such as infrastructure variables, prices and others. From the hypothesis test: The Relationship Marketing variable has a t statistic value of 3.498 and is greater than t table which is 2.010 (3.498 > 2.010) and the promotion variable has a t statistic value of 5.444 which is greater than t table which is 2.010 (5.444 > 2.010) means the hypothesis that filed